Managing Higher Education Pain Points for Knowledge and Innovation for Africa’s Development: Lessons from the Rest of The World - Taderera, Dr. Faustino (RA Journal of Applied Research, 2023)
The main thrust of this research was to contribute to theory building in the Pain Points Theory (PPT) and their applicability in African Higher Education Institutions (referred to as AHEI right through), with focus on colleges and universities. The research explored gaps in knowledge regarding this theory as a contribution to knowledge, and in this instance the AHEI was the sample and epicentre of the research and was expected to meet foremost the needs of industry and government as employers of graduated students, then the needs of students and society in knowledge and innovation. This research was conceptual research using literature review only. A Pain Point or constraint is anything that prevents the system from achieving its goal like poor funding, high teaching loads, unattractive research prizes and incentives, low salaries that drive away talented academics and others and finally poor resourcing. The main reasons giving rise to this research were the facts that some colleges and universities in Africa faced challenges in graduate employability and suitability for industry and funding and needed accreditation by government agencies, and some had low innovation and research output. The main objective of this research was to contribute to theory building in the Theory of Higher Education and PPT and identify critical success factors for efficiency in service delivery excellence to students, industry and society in line with market orientation philosophy. The secondary objective was employability of graduates as the end product, maximising knowledge creation and innovation. Qualitative research method in the form of conceptual research was used in this research. The main findings were low salaries were driving away academics to NICs and overseas developed countries, lack of practicals/diverse teaching methods, lack of compulsory internship, unfair assessment, balancing classes with free time, the need for diversity in terms of faculty, uncommitted students, incompetent faculty, outdated syllabus, students from high schools not being college ready, graduates not matching industry requirements, poor internet service, low knowledge creation, lower levels of innovation and industrialisation in Africa, unattractive prizes for researchers and same for research incentives, lack of apprenticeship in some countries and no research funding.